EFFECTIVENESS OF CRIMINAL FINES ON ILLEGAL FISHING CRIMINAL ACTIONS BY FOREIGN FISHING VESSELS (KIA) IN THE WATERS OF THE INDONESIAN EXCLUSIVE ECONOMIC ZONE (ZEEI) OF THE MALACCA STRAIT (STUDY OF DECISIONS IN THE MEDAN DISTRICT COURT, CLASS 1A SPECIAL) - Robert Napitupulu (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study aims to analyze the effectiveness of the application of criminal fines against perpetrators of illegal fishing by Foreign Fishing Vessels (KIA) in the waters of the Indonesian Exclusive Economic Zone (ZEEI) of the Malacca Strait based on a study of the decision of the Medan District Court Class 1A Special Fisheries Court. Indonesia as an archipelagic country has a wealth of fishery resources that are vulnerable to illegal fishing practices, especially by foreign-flagged KIA. In the international maritime law regime (UNCLOS 1982), coastal states such as Indonesia have sovereign rights to enforce the law in the ZEEI, but are limited by the prohibition on the application of imprisonment to foreign violators. Therefore, criminal fines are the main alternative in law enforcement. The results of the study show that of the 137 fisheries crime cases decided during the period 2015–May 2025, 66 cases involved KIA with the majority being sentenced to fines and confiscation of evidence. The effectiveness of fines is shown by the significant decline in the trend of cases in the last five years, as well as the deterrent effect on foreign perpetrators. However, challenges are still found related to the success of fine recovery and coordination between law enforcers. This study confirms that although fines have not been fully optimal in their implementation, they have substantively been able to contribute to the protection of fishery resources and Indonesia's legal sovereignty at sea. Consistent law enforcement and increasing the capacity of fisheries courts are absolute requirements in strengthening the national maritime supervision and justice regime.